Konseling Islami Berbasis Kisah Nabi untuk Meningkatkan Kemandirian Anak di RA Al-Kifayah Riau - Asmidaryani, Asmidaryani (Sekolah Tinggi Agama Islam Al-Kifayah Riau, 2025)
This study aims to increase children's independence and strengthen Islamic values ​​and offer novelty in the approach to early childhood counseling by integrating the stories of the Prophet as the main media. This study introduces a counseling model that is religious and contextual. The results of this study have significant practical implications for teachers, this approach can be a learning strategy as well as effective guidance in instilling values ​​of independence in a fun and meaningful way for children. The research method used is a qualitative descriptive case study approach. The subjects of the study included class teachers and students, while the object of the study was children's independence. Data collection techniques were carried out through observation, interviews, and documentation. Data analysis techniques used deductive and inductive approaches. The results of the study showed that through interviews with teachers, it was found that the story of the Prophet was considered more effective than the lecture method because children were more interested, focused, and easily remembered the values ​​conveyed. Children's independent behavior began to be seen from them imitating the characters in the story. The effectiveness of Islamic counseling through the story of the Prophet can be seen from children easily grasping the message and making children happier. In conclusion, the application of the Islamic counseling approach through the story of the Prophet has a positive influence on increasing the independence of early childhood